High resolution Ordovician carbon isotope chemostratigraphy in South China and its significance for global correlation - Gong, Fangyi; Luan, Xiaocong; Calner, Mikael; Lehnert, Oliver; Zhang, Yuchen; Yan, Guanzhou; Wei, Xin; Wu, Rongchang (Global and Planetary Change, 2024)
Based on the Shidi-1 drill core, this paper presents new and highly time resolved carbon isotope data (δ13Ccarb) for the Early Ordovician through Early Silurian of the Yangtze Platform, South China. Five carbon isotopic shifts (C1-C5) through the late Tremadocian to the Katian have been recognized in the Shidi-1 drill core recordings. Together with previously published isotope data, a composite carbon isotope curve for the Yangtze platform, permits the identification of a continuous Ordovician carbon isotope trend with five prominent carbon isotope shifts; including the TSICE, the Late Tremadocian positive Isotopic Carbon Excursion (LTICE, named herein), the Late Floian Rise, the MDICE and the Pagoda Isotopic Carbon Excursion (PICE, named herein). The identification and documentation of these anomalies further strengthen the regional and global correlation of the Ordovician succession on the Yangtze platform. The long-term trend in carbon isotopes indicates that organic carbon burial increased gradually throughout the Great Biodiversification Event (GOBE). A tipping point is also marked by the Dapingian-Darriwilian border, which is followed by a notable shift in the environment and creatures in the middle Darriwilian.
CRIS-Team Scopus Importer:2024-08-02
Keywords: Carbon isotope events; Global correlation; GOBE; Ordovician; South China